Ectopic hidradenoma papilliferum of eyelid: A rare entity with diagnostic challenge - Prakriti Shukla; Anil K Malaviya (Wolters Kluwer Medknow Publications, 2018)
Hidradenoma papilliferum is a rare cutaneous adnexal tumour of middle aged females arising mainly in the apocrine sweat glands of perianal and genital region. Ectopic forms of this entity have been described with majority of them occurring on the head and neck region. We report a case of 16 years young male who presented with two small, well circumscribed, greyish-brown, firm, nodules on his left upper and lower eyelid. A clinical impression of basal cell carcinoma was assumed but on histopathological examination it was diagnosed as hidradenoma papilliferum of eyelid. Immunohistochemistry was performed to support the diagnosis due to its unusual clinical presentation. To the best of our knowledge, only six cases in the upper eyelid and one case in the lower eyelid have been reported in the English literature. This is the first case report of hidradenoma papilliferum involving both upper and lower left eyelid in an adolescent boy.